MISKONSEPSI SISWA KELAS IV SD PADA MATERI WUJUD ZAT DAN PERUBAHANNYA - Muhammad Yazid Fatkhul Mujib; Heru Purnomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Misconceptions are one of the main barriers in learning Natural Science (IPA) in elementary schools, especially regarding the matter of states of matter and their changes. A misunderstanding of basic concepts can lead to difficulties for students in studying advanced IPA material. This study aims to identify the level of misconceptions among fourth-grade elementary school students regarding the topic of states of matter and their changes, as well as to provide an overview of which subtopics most frequently generate misconceptions. The method used is quantitative descriptive, employing a two-tier diagnostic test method consisting of multiple-choice questions and open-ended reasons. The research was conducted at Godean 2 Public Elementary School, with a total of 54 respondents from two classes. The results indicate that misconceptions occurred in all tested subtopics, with details: changes in states of matter (69%), types of states of matter (63%), and characteristics of states of matter (39%) The subtopic of changes in state of matter is the area with the highest level of misconceptions. Students have difficulty understanding scientific concepts such as the order of changes in state, the difference between evaporation and boiling, and the effect of temperature on substances. These results indicate the need for more contextual and visual learning, such as direct demonstrations, simple experiments, and the use of digital media. Routine use of diagnostic tests is also recommended to detect and address misconceptions early to support better understanding of science concepts.